Analysis of Work Environment Management in Supporting User Safety and Comfort at Duren Kalibata Station - Sulandari, Uci; Sayuti, Rizky Ahmad; Prabowo, Lungguh Budi; Rozi, Fikri Al Ghifari (International Journal of Advanced Multidisciplinary, 2026)
Duren Kalibata Station is a public transportation facility with high operational activity, potentially creating various work environment risks which can impact user safety and comfort. Proper work environment management is necessary to minimize potential hazard and support a safe and orderly station environment. This research aimed to analyze work environment management at Duren Kalibata Station to support safety aspect. The method used was descriptive qualitative through direct observation, interview, and documentation study. The results indicated that work environment management at Duren Kalibata Station included cleanliness management, waste control, public facility arrangement, and the implementation of safety signs and facilities. Overall, work environment management had been quite successful, but several aspects needed improving, such as consistent station area cleanliness and optimization of safety support facilities. It was expected that the results of this research were able to provide evaluation material and recommendations for management in improving work environment management to support safety at Duren Kalibata Station.